APLIKASI TEKNIK BUDI DAYA JAMUR TIRAM DAN MANAJEMEN USAHA UNTUK MENINGKATKAN KESEJAHTERAAN PETANI JAMUR TIRAM DI BADUNG –BALI - Ida Bagus Swaputra; Wayan Arya Paramarta (Forum Manajemen STIMI Handayani Denpasar, 2015)
IbM is one of program that driven community to gain the better productionprocess and management. Thus scheme funded by the Directorate General of HigherEducation. The partner of this program is on SME mushroom community cultivatorsin the district Mengwi Badung ea. Tri Putrimushrom and Artana mushrom . Themain problem faced by SMEs partner is a lack of understanding of the partners oystermushroom cultivation techniques, so often happens baglog mushroom seed can notdevelop properly so that the oyster mushroom yields declined. On the other handoyster mushroom demand for traditional markets and other consumers continue toincrease. The oyster mushroom cultivationas a sideline business, but it requiresa fairly high investment cost to build a house nursery, wooden shelves for baglogmushrooms and mushroom seed investment .The next problem faced is the lack oftrained partners in cultivation technology, the partneralso still low inaccountingtechniques as currently partner SMEs have never know for sure whether its businessat a profit or even get a loss . The methods used in carrying out the program is amethod of training with focus group discussion and participation action research,After this program run out, the partner is increasing of mushroom cultivation andunderstanding of business management is increasing, eventually the productivityof oyster mushroom production can be increased, and income level directly SMEspartners be increased as well.